Serum Protein Electrophoresis: An Important Tool for Diagnosis and Monitoring of Plasma Cell Neoplasms - Dutta, Bijita; Chauhan, Garima (Medicine and Medical Research: New Perspectives Vol. 8, 2024)
Serum Protein Electrophoresis (SPEP) is a widely used test besides bone marrow aspiration and biopsy for diagnosing and monitoring plasma cell neoplasms. Immunofixation electrophoresis (IFE) is done to complement SPEP. Both of them have a distinct role in the management of plasma cell neoplasms as per international guidelines. Understanding the SPEP patterns associated with various plasma cell neoplasms and recognizing the significance of its quantitative evaluation is crucial for accurate diagnosis and therapy monitoring. SPEP and IFE are done utilizing different methodologies, e.g., Agarose gel electrophoresis and capillary zone electrophoresis. In this chapter, different patterns of SPEP as found in agarose gel electrophoresis system, Sebia Hydrasis 2 Scan Focusing System® was elaborated. The complementary role of SPEP and IFE in the diagnosis and monitoring of plasma cell neoplasms was also discussed.